Pemanfaatan Media Wordwall dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Pendidikan Agama Islam - Zakiatur Riskiyah; Muliatul Maghfiroh (Kartika: Jurnal Studi Keislaman, 2026)
Low student learning motivation remains a common problem in Islamic Religious Education (IRE) learning, requiring instructional innovation through the use of media that can actively engage students. One medium that can be utilized is Wordwall, a digital learning platform that provides various interactive activities such as quizzes, educational games, puzzles, and practice exercises. This study aims to describe the implementation of Wordwall in improving students’ learning motivation and to identify obstacles encountered in its application in IRE learning at SMK Negeri 1 Tlanakan. This research employed a qualitative approach with a descriptive design. The research subjects included the principal, IRE teachers, and tenth-grade students of Industrial Chemical Engineering. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis involved data reduction, data display, and conclusion drawing. The findings indicate that the use of Wordwall can enhance students’ learning motivation, as reflected in increased participation, interest, and enthusiasm during learning activities. The learning process becomes more interactive and enjoyable; however, challenges such as limited supporting devices and unstable internet connections were still encountered